Clinical value of immunohistochemical assessment of expression of p53, Bcl-2 and Bax proteins in Non Small Cell Lung Cancer Review - Faran, Grzegorz; Dworakowska, Dorota; Jassem, Ewa (Contemporary Oncology/Współczesna Onkologia, 2004)
Lung cancer is the main cause of death due to neoplasms in Poland. Understanding of the lung cancer biology may result in a better selection of patients for combined therapy and new therapeutic strategies. According to the previous studies, abnormalities of programmed cell death (apoptosis) can accelerate the progress of the non small cell lung carcinoma (NSCLC). A review indicates the role of proteins involved in apoptosis in lung carcinogenesis. P53, Bcl-2 and Bax control a number of molecular pathways (cell cycle, DNA synthesis, apoptosis and others). Thus, an abnormal expression of these proteins is considered as one of the most important carcinogenesis mechanisms. The clinical value of immunohistochemical assessment of expression of p53, Bcl-2 and Bax proteins in NSCLC is also reviewed. Some studies showed that overexpression of p53 has an adverse effect on the prognosis, whereas the overexpression of Bcl-2 usually improves the prognosis in NSCLC. The role of Bax expression in NSCLC has not been established yet. The practical use of those data requires further studies.